Association between SARS-CoV-2 Infection and Adverse Perinatal Outcomes by Race/Ethnicity in a Large Integrated Health Care System - Mensah, Nana A.; Fassett, Michael J.; Lurvey, Lawrence D.; Oyelese, Yinka; Braun, David; Sacks, David A.; Shi, Jiaxiao; Khadka, Nehaa; Chiu, Vicki Y.; Peltier, Morgan R.; Getahun, Darios (American Journal of Perinatology, 2024)
Objective Recent studies have reported associations between severe acute respiratory syndrome-coronavirus-2 (SARS-CoV-2) infection during pregnancy and adverse perinatal outcomes but the extent to which these associations vary by race/ethnicity remains uncertain. Therefore, we examined how the association between prenatal SARS-CoV-2 infection and adverse perinatal outcomes may be modified by race/ethnicity.Study Design A retrospective cohort study was performed using data on 67,986 pregnant women extracted from the Kaiser Permanente Southern California electronic health records between April 6, 2020, and December 31, 2021. Upon admission to labor and delivery, all women were routinely tested for coronavirus disease 2019 (COVID-19) using real-time reverse-transcriptase polymerase chain reaction test. Adjusted odds ratios (aORs) were used to estimate associations.Results During the study period, COVID-19 was diagnosed in 4,960 (7%) of singleton pregnancies, with the highest rates observed among Hispanics (9.4%) and non-Hispanic Blacks (6.2%). Compared with non-Hispanic Whites, Hispanics (aOR: 1.12, 95% CI: 1.03, 1.21) with SARS-CoV-2 infection had the highest odds of a pregnancy associated with nonreassuring fetal heart rate tracing. Neonates of all races/ethnicities, except for non-Hispanic Blacks, showed significantly increased odds of SARS-CoV-2 infection, with the highest risk observed among Asians/Pacific Islanders (aOR: 10.88, 95% CI: 1.33, 89.04). Non-Hispanic White mothers who tested positive were admitted to intensive care unit (ICU) at a higher rate at delivery and within 7 days of delivery (aOR: 34.77, 95% CI: 11.3, 107.04; aOR: 26.48, 95% CI: 9.55, 73.46, respectively). Hispanics were also at a significantly higher odds of admission to ICU (aOR: 4.62, 95% CI: 2.69, 7.94; aOR: 4.42, 95% CI: 2.58, 7.56, respectively). Non-Hispanic Black, Hispanic, and Asian/Pacific Islander mothers who tested positive for SARS-CoV-2 prenatally, were at increased risk for preeclampsia/eclampsia, and preterm birth as compared to non-Hispanic White mothers.Conclusion The findings highlight racial/ethnic disparities in the association between SARS-CoV-2 infection and adverse perinatal outcomes. The risk of neonatal SARS-CoV-2 infection was highest for Asian/Pacific Islanders. We also observed a remarkably high risk of ICU admission for non-Hispanic White mothers infected with SARS-CoV-2.Key Points
Keywords: COVID-19; perinatal outcome; race